RME Learning Model in Urban And Rural Elementary Schools: A Comparative Study - Yunita Miftahul Jannah; Vinta Angela Tiarani (STAI Hubbulwathan Duri, 2023)
This study aims to (1) determine the application of Realistic Mathematics Education (RME) learning model in urban and rural elementary schools, (2) describe the comparison of the application of RME learning model in urban and rural elementary schools. The research was conducted at urban and rural elementary schools. The research participants were school principals, class teachers, and students. Data collection techniques were participatory observation, interviews, and document analysis. The validity of the data in this study was carried out by testing the credibility, transferability test, dependability test and confirmability test. Data analysis uses the Miles and Huberman models. The results showed that the application of the RME learning model at urban and rural elementary schools applied almost the same aspects. The difference is that urban elementary schools emphasize the principle of guided discovery, and rural elementary schools put forward the principle of connecting informal knowledge to formal mathematical knowledge. The implementation characteristics of the RME learning paradigm were similar in both Elementary Schools. Those elementary schools underwent the same four stages during the implementation phase. The application element exhibited the most notable disparity. The urban primary school extensively utilised contemporary and readily available media, equipment, and teaching resources. Meanwhile, the rural primary school implemented environment-based media and other instructional materials. The mathematics learning outcomes in both elementary schools were equitable. The RME learning concept is applicable in both urban and rural schools.